THE EXTENDED FUZZY LINEAR COMPLEMENTARITY PROBLEM - NAGOORGANI, A.; SUDHA, K. (International Journal of Mathematical Archive, 2018)
In this paper the Extended Fuzzy Linear Complementarity Problem (EFLCP),an extension of the well-known Fuzzy Linear Complementarity Problem(FLCP) is defined. The general solution set of an EFLCP is discussed and an algorithm to find the solution is suggested. Finally the applications of EFLCP in the max algebra are discussed with a numerical example by using a triangular fuzzy number.